An Analysis of Low Achiever Students’ Difficulties in Learning English at SMA Negeri 7 Bulukumba - Nurul Latifa Amin; Muhammad Tahir; Muhammad Arham Basr (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study focuses on the difficulties faced by low achiever students in learning English at SMA Negeri 7 Bulukumba, a rural school with limited educational resources. Using a descriptive qualitative case study, data were gathered from five low-performing students and two English teachers through interviews, observations, and documentation. Findings reveal that internal issues, such as low motivation, poor vocabulary, and grammatical difficulties, are compounded by external factors, including inadequate support, traditional teaching methods, and the unproductive use of technology. Although digital tools have potential, limited digital literacy and infrastructure hinder their effectiveness. The study calls for contextualized teaching, teacher training, and improved technological support to enhance English learning for low achievers in rural areas.